Acute copper overload induces vascular dysfunction in aortic rings due to endothelial oxidative stress and increased nitric oxide production. Issue 8 (18th April 2018) - Nunes, Karolini Zuqui; Fioresi, Mirian; Marques, Vinicius Bermond; Vassallo, Dalton Valentim
ABSTRACT: The mechanisms involved in vascular reactivity alterations promoted by copper (Cu) overload were investigated. Thoracic aorta obtained from male Wistar rats were cut into rings and exposed for 1 h to 10 µg/ml Cu. Exposure to Cu decreased the contractile responses of aortic rings to phenylephrine (PHE). Removal of endothelium and subsequent administration of N-nitro-L arginine methyl ester (L-NAME), tetrahydrobiopterin, aminoguanidine, diethyldithiocarbamic acid, catalase, or tetraethylammonium increased contractile responses. Incubation with apocinyn and tiron enhanced the sensitivity to PHE. Data demonstrated that high concentrations of Cu reduced PHE-mediated vascular reactivity which was associated with elevated production of nitric oxide (NO), which was attributed to activation of inducible NO synthase, and elevated levels of hydrogen peroxide probably related to a rise in superoxide dismutase activity and reactive oxygen species generation.